Preliminary Study of Photocatalytic Degradation of Methylene Blue Dye using Magnetic Alginate/Fe3O4 (Alg/Fe3O4) Nanocomposites - Ganjar Fadillah; Muhamad Allan Serunting (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2019)
The Magnetic compound, Fe3O4, is one of the compounds that is easily hydrolyzed and oxidized. A coating method was presented in this study to prevent the process. The modifications of Fe3O4 were carried out by supporting alginate as natural polymers on the surface of Fe3O4. Preparation of magnetic alginate/Fe3O4 (Alg/Fe3O4) nanocomposite has been successfully synthesized. Alg/Fe3O4 material was synthesized using the coprecipitation method with Fe2+; Fe3+ (with molar ratio 1:2) and alginate 1% as precursors. Synthesized Alg/Fe3O4 nanoparticles were characterized by Fourier Transform Infrared Spectroscopy (FTIR), DelsaTM Nano C Particle Analyzer, Transmission Electron Microscopy (TEM), Scanning Electron Microscopy (SEM), and Energy Dispersive Spectroscopy (EDS). The Alg/Fe3O4 has an average diameter of 13.70 nm. Photodegradation test of synthetic methylene blue (MB) dye was found at pH 5.0 and irradiation time under UV245 for 60 minutes. The degradation results showed that the percentage of MB dye removal reached more than 90%.